2022
DOI: 10.3390/antiox11010155
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation with Tea Residues Enhances Antioxidant Activities and Polyphenol Contents in Kombucha Beverages

Abstract: Kombucha is a popular beverage with various bioactivities (such as antioxidant activity), which can be attributed to its abundant bioactive compounds, especially polyphenols. Kombucha is conventionally prepared by fermentation of a sugared black tea infusion without tea residue. In this study, the effects of black tea residue and green tea residue on kombucha were studied, and its antioxidant activities, total phenolic contents, as well as concentrations of polyphenols at different fermentation stages were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 38 publications
8
58
2
Order By: Relevance
“…Numerous studies have shown that alternative raw materials could allow the kombucha beverages significant antioxidant activities and increase the amounts of bioactive compounds [ 10 , 23 , 24 ]. Moreover, fermentation with tea residues was found to increase antioxidant capacities as well as polyphenol contents of kombucha [ 12 ]. Therefore, in this study, we adopted vine tea and sweet tea to develop new kombucha beverages, and compared the effects of kombucha beverages fermentation with or without tea residues.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies have shown that alternative raw materials could allow the kombucha beverages significant antioxidant activities and increase the amounts of bioactive compounds [ 10 , 23 , 24 ]. Moreover, fermentation with tea residues was found to increase antioxidant capacities as well as polyphenol contents of kombucha [ 12 ]. Therefore, in this study, we adopted vine tea and sweet tea to develop new kombucha beverages, and compared the effects of kombucha beverages fermentation with or without tea residues.…”
Section: Resultsmentioning
confidence: 99%
“…The concentrations of bioactive components in kombucha beverages were measured by HPLC-PDA based on previous studies [ 12 , 17 ]. Separation was performed using an Agilent Zorbax Eclipse XDB-C18 column (250 mm × 4.6 mm, 5 µm) (Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacteria are from the genera Acetobacter and Gluconobacter , while the yeast is Mycoderma , Mycotorula , Pichia , Kloeckera , Brettanomyces , Torulospora , Candida , Schizosaccharomyces , Saccharomycodes , Zygosaccharomyces , and Saccharomyces [ 172 ]. The beverage has a sour and sweet taste based on the type of starter, and the flavor comes from tannin transformation [ 173 ]. Kombucha herbal tea is famous for its antioxidant and antimicrobial activities [ 174 ].…”
Section: The Prospect Of Mangrove Fruit In the Functional Food Develo...mentioning
confidence: 99%